Unions-LMC relationships in selected companies in the Philippines - Gonzaga, Jenny Sta. Maria 1982- (2008)
Specifically, the study sought to answer the following: 1)What is the current state of unionism and Labor Management Councils (LMCs) in the Philippines? 2) How does the rise of LMCs affect Unions? 3)How do unions react to LMCs? 4) What is the relationship between unions and LMCs in the selected companies? 5) How do union and management rate the effectiveness of LMCs in the workplace? and, 6) What approaches can be done to maximize the roles of Unions and LMCs and combine their efforts towards greater cooperation in the workplace?...